(untitled) (Revista de História Regional, 2024)
In Portugal, tackling childhood poverty was understood as essential, not only to combat “social evils”, considering new hygienist precepts, but also as a defense of a concept of improving the race. The moralization of the poor from childhood was then imposed as a responsibility of the State, forcing the creation of institutions of social and hygienic educational assistance, based on scientific and pedagogical concepts that did not escape Darwinist and eugenic influences. The then dominant corrective pedagogies, focused on responses in the field of moral and therapeutic education for children in situations of poverty, when many of their shortcomings were social and environmental, go in the same direction. The purpose of this study aims to explain the emergence and trajectory of social policies to tackle child poverty, invoking the central role of policy makers in receiving ideas, science and knowledge produced about childhood during the First Republic in Portugal. Specifically, the aim here is to highlight the social, political and cultural context of the emergence of the Child Protection Law of May 27, 1911. It is our intention to establish convergences or divergences between the theoretical influences of Herbert Spencer’s social Darwinism and the opportunity to create a Law that is still considered significant and a historic landmark in terms of children’s rights and protection.